Analysis of the Physical Chemical Characteristics of Chicken Sausages with the Addition of Sengkubak Leaves (Pycnarrhena cauliflora (Miers) Diels) - Monasdir, Monasdir; Nugroho, A Adhityawan; Riskayanti, Riskayanti; Husein, Firdaus; Nisfimawardah, Lailatun; Astuti, Erlina (Faculty of Animal Science Universitas Brawijaya, 2026)
This study aims to analyze the physical and chemical characteristics of chicken sausages with the addition of sengkubak leaves (Pycnarrhena cauliflora (Miers) Diels). The experimental design used in this study was a Complete Randomized Design (RAL) consisting of 2 treatments with differences in the concentration of adding fresh sengkubak leaves, namely T0 (chicken sausage without the addition of sengkubak leaves), T1 (chicken sausage + 2% sengkubak leaves) and T2 (chicken sausage + 4% sengkubak leaves) with each treatment repeated as many as 3 repeats. Observed variables physical characteristics of chicken sausages (pH, Aw value). Chemical and antioxidant characteristics of Sengkubak leaves sausage (moisture content, protein content and antioxidants) Data on physical, chemical, antioxidant characteristics of chicken sausages with the addition of sengkubak leaves were analyzed using ANOVA and further tested using the Tukey test. The results showed that chicken sausage with the addition of sengkubak leaves at different levels had an effect on the value of pH, Aw, water content, protein content, and antioxidants. The addition of sengkubak leaves increases the antioxidant levels of chicken susages and makes the greenish color compared to without the addition of sengkubak leaves. Sengkubak leaves can be effectively utilized as a functional ingredient to improve the nutritional value and antioxidant capacity of chicken sausages without compromising their physicochemical quality. These findings highlight the potential application of sengkubak leaves in the development of value-added meat products with enhanced health benefits.